Operations and supply chain management - Russell, Roberta S.; Taylor, Bernard W. (Wiley, 2019)
Russell and Taylor's Operations and Supply Chain Management, 10th Edition is designed to teach students understand how to create value and competitive advantage along the supply chain in a rapidly changing global environment. Beyond providing a solid foundation, this course covers increasingly important OM topics of sustainability, corporate social responsibility, global trade policies, securing the supply chain, and risk and resilience. Most importantly, Operations Management, Tenth Edition makes the quantitative topics easy for students to understand and the mathematical applications less intimidating. Appropriate for all business students, this course takes a balanced approach to the foundational understanding of both qualitative and quantitative operations management processes.